OS RECURSOS SEMIÓTICOS EM VÍDEO-RESENHAS DE BOOKTUBERS COMO ESTRATÉGIA DE INCENTIVO À LEITURA - Vargas, Janete Correia (2018)
Currently, the program content of Literature for High School is still based on teaching the classics of Brazilian Literature, which creates a barrier for literature teachers who need to encourage students to read these classics. To contribute with this incentive, teachers rely on booktubers, that is young people who talk about literature and who produce video-reviews, attracting thousands of teenagers and adults to the literary channels of YouTube. In this sense, the present work sought to analyze the semiotic resources used by booktubers as strategies to encourage the reading of the Brazilian Literature classics, initially, started with a bibliographical revision of the blog concepts to YouTube, as well as, authors that discuss and support the analyzes that are present in this work. The theoretical support used for the analysis of semiotic resources is the Visual Design Grammar (GDV), by Kress and van Leeuwen (2006), from the perspective of interactive metafunction, and from the four dimensions used in the interaction process: Social distance, Perspective and Modality, discussed by the perspective of the Multimodal Discourse Analysis (ADM) (Kess, Van Leeuwen, 2001). The following videos were analyzed: "Dom Casmurro", from the "Ler antes de Morrer" channel, from the booktuber Isabella Lubrano and "O Cortiço" from the "Vá Ler Um Livro" channel from the Tati booktuber, being these videos the most visual ones referring to Brazilian Realism. After analyzing the four dimensions of the interactive metafunction, it is possible to consider that the semiotic resources used by the booktubers in the videos produced by them, are able to effectively interact with the young audience and encourage them to read the classics of Brazilian Literature.